Autopsy Findings in Conjoined Twin with Single Heart and Single Liver - Kar Asaranti; Mohanty Pranati; Kar Tushar; Behera Jagadish; Behera Susmita; Nayak Amarendra (Case Reports in Pathology)
Thoracoomphalopagus is the commonest type of conjoined twin where the bodies are fused from upper chest to lower chest. The autopsy done can help counsil the parents for further pregnancies and determine the prognosis depending upon the type of cardiac anomaly by Seo classification when detected antenatally. We describe the detail pathological autopsy of such a case with single heart and single liver. A detail autopsy was done on the twin fetus. The twins shared a single heart and sometimes the liver and part of digestive system. The combined weight was 4.1 KG. Both were full-term male babies joined from below the nipple till umbilicus. Autopsy in conjoined twins helps in deciding the type of fusion of the body and also of the heart and great vessels. It can help in counseling parents about future pregnancies that there is no chance of recurrence of this abnormality and no need to be scared.